2020
DOI: 10.1109/access.2020.2984178
|View full text |Cite
|
Sign up to set email alerts
|

Gamification for Recruitment and Job Training: Model, Taxonomy, and Challenges

Abstract: The recruitment, engagement, and training of the employees are among the core and critical roles for running an organization successfully. Gamification has been proven to be a promising tool that offers many innovative solutions for various domains. This study presents a systematic literature review (SLR) of research studies involving gamification for recruitment, engagement, and training of employees. The SLR has been synthesized by reviewing carefully selected research studies published between 2014 and 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 51 publications
(65 reference statements)
0
28
0
5
Order By: Relevance
“…Researchers have provided useful review articles on other areas including Introductory Programming Language (Mehmood et al, 2020 ), use of gamification (Obaid et al, 2020 ), research trends in the use of enterprise service bus (Aziz et al, 2020 ), and the role of IoT in agriculture (Farooq et al, 2019 , 2020 ) However, to the best of our knowledge, no such study was found in the area of database systems education. Therefore, this study discusses research work published in different areas of database systems education involving curricula, tools, and approaches that have been proposed to teach an introductory course on database systems in an effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have provided useful review articles on other areas including Introductory Programming Language (Mehmood et al, 2020 ), use of gamification (Obaid et al, 2020 ), research trends in the use of enterprise service bus (Aziz et al, 2020 ), and the role of IoT in agriculture (Farooq et al, 2019 , 2020 ) However, to the best of our knowledge, no such study was found in the area of database systems education. Therefore, this study discusses research work published in different areas of database systems education involving curricula, tools, and approaches that have been proposed to teach an introductory course on database systems in an effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Gamification is also used in corporate training as an important part of their learning strategies. Employers find that this practice provides the trainees with better recall and retention, helps to improve performance and provides a safe environment to practice and obtain the required skills (Obaid, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is not the grail of the study, as the elaborated study of articles/papers is not here. The main objective is having classification, content analysis and recognition of publishing forums [68] [69].…”
Section: Methodsmentioning
confidence: 99%